Influencing factors of methane emission dynamics at different water depths in hangzhou bay reed wetland, China. Issue 5 (16th June 2017) - Shao, Xuexin; Sheng, Xuancai; Wu, Ming; Wu, Hao; Ning, Xiao
Abstract : Water depth (WD) influences wetland methane (CH4 ) emissions by affecting plant growth and the physical and chemical properties of soil. We studied the factors influencing CH4 emission dynamics at different WD in reclaimed reed wetland in Hangzhou Bay, China. The annual average WD was set as WD0 (0 cm), WD1 (10 cm), WD2 (20 cm), and WD3 (35 cm). The transparent chamber–gas chromatography method was used to determine CH4 fluxes during the growing season. Results showed that the average CH4 flux was 7.03 mg m −2  h −1, and that CH4 fluxes under all 4 WDs presented as a CH4 source. CH4 emissions of the reed wetland showed obvious seasonal changes; summer was the peak period for CH4 emissions. In a vigorous growth period of reeds, the CH4 flux gradually increased as WD increased. However, in early and late growth periods of reed, CH4 flux first increased (WD0 < WD1 < WD2) then decreased (WD2 > WD3) as WD increased. Correlation analysis showed that at the 4 WDs, CH4 flux was significantly, positively correlated with air temperature, soil temperature, and aboveground biomass of reeds, and were highly significantly positively correlated with water temperature. In addition, at WD0, CH4 flux also showed a significant, positive correlation with soil organic carbon content in the 0–5 and 5–10 cm soil layers, and was significantly negatively correlated with soil water content. Hence, WD significantly influenced wetland CH4 emissions. Temperature and biomass were major influencing factors of CH4 emission in reed wetland at different WDs. © 2017 American Institute of Chemical Engineers Environ Prog, 36: 1301–1307, 2017